2001
DOI: 10.1002/jcc.10018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying native‐like protein structures using physics‐based potentials

Abstract: As the field of structural genomics matures, new methods will be required that can accurately and rapidly distinguish reliable structure predictions from those that are more dubious. We present a method based on the CHARMM gas phase implicit hydrogen force field in conjunction with a generalized Born implicit solvation term that allows one to make such discrimination. We begin by analyzing pairs of threaded structures from the EMBL database, and find that it is possible to identify the misfolded structures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 77 publications
8
98
0
Order By: Relevance
“…GB models have been used successfully for calculating accurate solvation energies of small molecules, 51,59,62 scoring of protein conformations, [63][64][65] evaluation of protein-ligand binding, 66 pK a predictions, 54 and implicit solvent molecular dynamics simulations. 55,66 -69 However, problems in achieving stable trajectories of native conformations when using GB for simulations have also been pointed out.…”
Section: Approximation Of Poisson Theory Through Generalized Born Formentioning
confidence: 99%
“…GB models have been used successfully for calculating accurate solvation energies of small molecules, 51,59,62 scoring of protein conformations, [63][64][65] evaluation of protein-ligand binding, 66 pK a predictions, 54 and implicit solvent molecular dynamics simulations. 55,66 -69 However, problems in achieving stable trajectories of native conformations when using GB for simulations have also been pointed out.…”
Section: Approximation Of Poisson Theory Through Generalized Born Formentioning
confidence: 99%
“…Electronic mail: brooks@scripps.edu ͑PB͒ energies 14 -18 with average relative errors of less than 1% for the GBMV method 14 -16 when calculating solvation energies of proteins in water. The application of implicit solvent descriptions has been increasingly successful in simulation studies, 19,20 scoring of protein conformations, 21 estimates of pK a values, 22 and evaluation of protein-ligand binding free energies. 23 However, since many biological processes occur in low-dielectric environments such as cell membranes, there is a strong incentive to extend continuum approaches based on GB to such environments as well.…”
Section: ٌ͓͑Rٌ͒͑r͔͒ϭϫ4͑r͒ ͑1͒mentioning
confidence: 99%
“…The nature of these problems reinforces the point that the scoring function must be fast and accurate enough for good scoring performance, which provides motivation, challenge, and validation to the physics-based energy functions (e.g., modern molecular mechanics plus continuum dielectric solvent models). While there exists some evidence that a GB model might not help for this purpose (Morozov et al, 2003), a number of other studies have shown that the physics-based energy functions perform well in distinguishing native and near-native folds (Dominy and Brooks, 2001;Feig and Brooks, 2002;Felts et al, 2002;Zhu et al, 2003) and loop conformations (Fiser et al, 2002;Forrest and Woolf, 2003) from a large set of nonnative decoys. Recent examination of GB and PB implicit solvation models in the context of computational protein design revealed a systematic bias that the burial of polar amino acids in the protein interior is more favored than that of nonpolar ones, which can be problematic in protein design (Jaramillo and Wodak, 2005).…”
Section: Scoring Of Protein Conformationsmentioning
confidence: 99%